Penerapan Prinsip Kerjasama dalam Acara Madh Rasul pada Akun Youtube Iqra’ Al-Fadhaiyyah (Kajian Pragmatik) - Zahratul 'Aini; Yufni Faisol; Delami Delami (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
This paper describes the application of the theory of the principle of cooperation in a prayer competition event held by one of the famous television stations in Egypt, namely Iqra 'Al-Fadhaiyyah. The data from this research are theutterances delivered by all speech participants (jury, presenters, participants) who are in the event. Using thetheory coined by Paul Grice Herbeur, namely the theory of the principle of cooperation which includes four maxims (rules): maxim of quantity, maxim of quality, maxim of relevance and maxim of manner. Next, it discusses the factors that cause violations of the cooperative principle using the SPEAKING theory which was coined by Dell Hymes. The data obtained in this study were 59 pairs of utterances which included compliance with the principle of cooperation, violations of the principle of cooperation and the factors causing violations of the principle of cooperation.